Ruin, repair and the hinterland: adapting ruin in the east rand, ekurhuleni to form an ecology centre in the repair of post-extraction landscapes - Edgar, Jack Douglas (University of the Witwatersrand, Johannesburg, 2024)
The Witwatersrand Mining Belt, a vast 100 km stretch in Gauteng, South Africa, bears the scars of extensive mining. This study focuses on Springs, a town deeply marked by the extraction of resources such as gold, coal, and clay. The aftermath of these activities is a landscape marred by toxic mine tailings, contaminated soil, and disrupted water systems, leading to the decline of indigenous ecosystems and the spread of invasive species. Current industrial proposals suggest further exploitation of these areas as dumpsites, worsening the environmental predicament. This thesis explores the environmental impact of mining activities in the Witwatersrand Mining Belt, focusing on the town of Springs. It highlights the degradation of native ecological systems due to mining and associated industrial development. The study emphasises the need for sensitive handling of these damaged landscapes to protect the environment, communities, and the region’s delicate ecology. It critiques the current approach of viewing post-mining regions as wastelands destined for further degradation and waste management. The research proposes a shift towards renaturing these sites, aiming to resolve major environmental concerns and propagate ecological repair across the East Rand and Witwatersrand mining belt. The thesis underscores the potential for rewilding these post-extractive regions, recalling the forgotten landscape of the Witwatersrand and envisioning a industrial past become catalysts for ecological restoration and community development. The Gauteng City-Region Observatory (GCRO) sees considerable potential for rewilding to convert these post-mining landscapes into ecological treasures and community resources. This strategy not only seeks to mend environmental damage but also to address the socio-spatial inequalities resulting from apartheid-era planning, which have disproportionately impacted communities like Kwa- Thema located near these blighted lands. The suggested architectural intervention in Springs encompasses the formation of green corridors to link fragmented habitats and the development of a hub for ecological restoration and community learning. Employing sustainable design principles and materials salvaged from local demolition sites, my proposed intervention acts as a bridge between the ecological requirements of the landscape and the social needs of its inhabitants. By turning symbols of degradation into symbols of resilience, the project imagines a future where post-mining landscapes are rejuvenated, promoting both ecological health and community prosperity
A research report submitted in fulfillment of the requirements for the Master of Architecture, In the Faculty of Engineering and the Built Environment, Wits of Architecture and Planning, School of Architecture and Planning, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Post-Extraction; Post-mining; Architecture; SDG-11: Sustainable cities and communities